Agricultura familiar en el agro argentino: una contribución al debate sobre el futuro del campesinado - Paz, Raúl (European Review of Latin American and Caribbean Studies, 2011)
Family farming in agrarian Argentina: a contribution to the debate about the future of peasantryThe academic debate about family farming in Argentina has been almost exclusively focused on the Pampas region and has as its central focus the changes and dynamics that family operations have gone through within the framework of the processes of agrarian transformation. Census information for the Pampas region indicates a constant and substantial disappearance of these operations, specially the smallest ones. The natural laws of capitalist production in Pampas agriculture would seem to be in full force in view of the concentration of property and production and the intensification of capital accompanied by a breakdown of non-capitalist agrarian agents. However, when there is an attempt to implement these laws of capitalist development in other places in Argentina, such as in the northwestern region, different processes can be observed. This article attempts to give an explanation about the various levels of capitalist penetration and its influence on the processes of differentiating the various actors who make up family farming by comparing these two regions, especially the peasant sector situated in areas outside the Pampas.Resumen:El debate académico sobre la agricultura familiar en Argentina, se ha concentrado casi exclusivamente en la región pampeana y tiene como preocupación central los cambios y dinámicas que ha experimentado la explotación familiar en el marco de los procesos de transformación agraria. La información censal indica para la región pampeana una constante y fuerte desaparición de las explotaciones, especialmente de las más pequeñas. Las leyes naturales de la producción capitalista en el agro pampeano, puestas de manifiesto por la concentración de la propiedad y de la producción, por la intensificación del capital, acompañado por los procesos de descomposición de agentes agrarios no capitalistas, parecerían tener plena vigencia. Sin embargo, al pretender trasladar estas leyes del desarrollo capitalista a otras regiones del país, como la región del noroeste argentino, se observan procesos diferentes. El artículo intenta dar una explicación, a partir de la comparación entre esas dos regiones, sobre los distintos niveles de penetración capitalista y su influencia en los procesos de diferenciación de los distintos actores que componen la agricultura familiar, en especial el campesino ubicado en áreas extrapampeanas.